2008
DOI: 10.1002/mc.20451
|View full text |Cite
|
Sign up to set email alerts
|

Wild‐type APC regulates caveolin‐1 expression in human colon adenocarcinoma cell lines via FOXO1a and C‐myc

Abstract: Genetic evidence suggests that caveolin-1, an essential component of membrane caveolae, acts as a tumor promoter in some, and a tumor suppressor in other cancers. The role of caveolin-1 in colon carcinogenesis is controversial. We report here, for the first time, that caveolin-1 is transcriptionally induced in colon cancer cells in response to conditional expression of a full length adenomatous polyposis coli (APC) gene. This induction of caveolin-1 by APC is mediated by both FOXO1a, a member of the Forkhead f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…The induction of caveolin-1 by APC is mediated by both FOXO1a, a member of the forkhead box family of transcription factors, and c-myc. 49 CAV1 expression is regulated by the ETS family of transcription factors through an ETS-binding DNA motif on the caveolin-1 promoter in lung epithelial cells. 50 An earlier study suggested that an ETS family transcription factor, Net, may suppress CAV1 transcription in primary lung tumors, and PEA3 may activate CAV1 transcription in metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of caveolin-1 by APC is mediated by both FOXO1a, a member of the forkhead box family of transcription factors, and c-myc. 49 CAV1 expression is regulated by the ETS family of transcription factors through an ETS-binding DNA motif on the caveolin-1 promoter in lung epithelial cells. 50 An earlier study suggested that an ETS family transcription factor, Net, may suppress CAV1 transcription in primary lung tumors, and PEA3 may activate CAV1 transcription in metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to CAV1 regulation by Adenomatous polyposis coli (APC) [16,17], which is frequently mutated in CRC [18]. The transcription factor FOXO1a, which is increased by wild-type APC expression, induces CAV1 expression, whereas the c-Myc protein, which is reduced in the presence of wild-type APC, represses CAV1 expression in colorectal carcinoma cells [16]. Friedrich T et al reported that deficiency of CAV1 in Apc min/þ mice promotes colorectal tumourigenesis and CAV1 mRNA and protein levels were diminished in the tumors compared with the healthy colonic tissues of these mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…About 45-70% of human colon cancers show reduced expression of CAV1 [14,15] and the reduction is more frequent in stage-I and II tumors [14]. This may be due to CAV1 regulation by Adenomatous polyposis coli (APC) [16,17], which is frequently mutated in CRC [18]. The transcription factor FOXO1a, which is increased by wild-type APC expression, induces CAV1 expression, whereas the c-Myc protein, which is reduced in the presence of wild-type APC, represses CAV1 expression in colorectal carcinoma cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study demonstrated that reintroduction of full length APC transcript into human colon tumor cells results in upregulation of CAV1. 41 The study suggests a mechanism by which CAV1 expression is regulated downstream of APC. Mutations in the APC gene are early genetic lesions in almost all cases of colorectal cancer.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 93%